Inductive Model of Science and Inductive Logic of R. Carnap - Nekrašas, Evaldas (Problemos, 1975)
The inductive model of science, its development and relation to the deductive model and connection between induction and probability are discussed in the paper. Principles of construction, the structure of R. Carnap’s inductive logic and conditions of adequacy of explication of the concept of logical probability are investigated. The author contends that three out of the five known conditions, contrary to R. Carnap’s and J. Kemeny’s opinion, are not self-evident and the remaining two are too vague to be conditions of adequacy for the explicatum. The author analyses identification of the degree of confirmation with probability and discusses the application problem of the inductive logic. The conclusion is drawn that R. Carnap’s inductive logic (in both of its variants, 1950-52 and 1971) is not a methodologically significant model of the factual procedures of confirmation of scientific theories.